1997
DOI: 10.1161/01.atv.17.10.1885
|View full text |Cite
|
Sign up to set email alerts
|

Normolipidemic Subjects With Low HDL Cholesterol Levels Have Altered HDL Subpopulations

Abstract: Epidemiological studies have established that plasma concentration of HDL is inversely correlated with the risk of coronary heart disease, even in the absence of increased LDL cholesterol levels. We postulate that specific HDL subpopulations may be responsible for antiatherogenic properties of HDL. HDL subpopulations were quantitated by two-dimensional gel electrophoresis in 79 normolipidemic healthy male subjects. To eliminate the influence of diet, volunteers consumed an average American diet for 6 weeks. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 37 publications
2
33
0
1
Order By: Relevance
“…The main disadvantage of the protein staining by Coomassie blue is that the method cannot be quantitative; to our knowledge, there is no procedure that selectively assesses HDL-total protein in plasma. The protein fraction, particularly apo AI of HDL, has been used for the quantifi cation of HDL subclasses in two-dimensional electrophoresis ( 10 ). Other components of HDL such as phospholipids and triglycerides may also be used in the quantifi cation of subclasses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main disadvantage of the protein staining by Coomassie blue is that the method cannot be quantitative; to our knowledge, there is no procedure that selectively assesses HDL-total protein in plasma. The protein fraction, particularly apo AI of HDL, has been used for the quantifi cation of HDL subclasses in two-dimensional electrophoresis ( 10 ). Other components of HDL such as phospholipids and triglycerides may also be used in the quantifi cation of subclasses.…”
Section: Discussionmentioning
confidence: 99%
“…NMR, vertical autoprofi le-II (VAP-II), as well as selective precipitation are based on HDL lipid content for estimating subclasses ( 5,8,17,18 ), whereas protein is the HDL component determined in other methods, such as two-dimensional electrophoresis ( 10 ) and PAGE in native conditions ( 17 ). Because small HDL particles are protein rich and lipid poor, whereas large particles are the contrary, the relative proportion of HDL subclasses is dependent on the component determined for the quantification.…”
Section: Enzymatic Staining Of Cholesterol On Polyacrylamide Gelmentioning
confidence: 99%
“…Others have also revealed that low HDL-C levels are independent risk factors for atherosclerotic vascular disease 30 . It has been reported that individuals with low HDL-C have an abnormal HDL sub-class distribution, with lower levels of large particles and increased levels of small HDL 31 . This abnormality in HDL sub-populations is associated with CHD prevalence 32 and increased recurrence of coronary events 33 .…”
Section: Hdlmentioning
confidence: 99%
“…Two-dimensional nondenaturing agarose-polyacrylamide gel electrophoresis and image analysis to determine the apoA-I-containing HDL subpopulations were carried out on plasma previously stored at Ϫ 80 Њ C as described (20,21). Briefly, in the first dimension, HDL particles were separated on an agarose gel according to charge.…”
Section: Hdl Subpopulation Analysismentioning
confidence: 99%